Analysis of Photosynthetic Characteristics and UV-B Absorbing Compounds in Mung Bean Using UV-B and Red LED Radiation. (11th February 2014) - Li, Fang-Min; Lu, Zhi-Guo; Yue, Ming
Abstract : Mung bean has been reported to have antioxidant, antidiabetic, anti-inflammatory, and antitumor activities. Various factors have important effects on the types and contents of plant chemical components. In order to study quality of mung bean from different light sources, mung bean seedlings were exposed to red light-emitting diodes (LEDs) and ultraviolet-B (UV-B). Changes in the growth parameters, photosynthetic characteristics, the concentrations of chlorophyll a and chlorophyll b and the content of UV-B absorbing compounds were measured. The results showed that photosynthetic characteristics and chlorophyll a and chlorophyll b concentrations were enhanced by red LEDs. The concentrations of UV-B absorbing compounds were enhanced by UV-B on the 20th day, while photosynthetic characteristics, plant length, and the concentrations of chlorophyll a and chlorophyll b were reduced by UV-B on the 40th day; at the same time the values of the stem diameter, plant fresh weight, dry weight, and the concentrations of UV-B absorbing compounds were enhanced. It is suggested that red LEDs promote the elongation of plant root growth and photosynthetic characteristics, while UV-B promotes horizontal growth of stems and the synthesis of UV-B absorbing compounds.